Kai kurie nauji duomenys apie L. Ivinskio kalendorių leidimą - Petkevičiūtė, Danutė (Knygotyra, 1970)
Conditions in which the Lithuanian calendars by L. Ivinskis were published are revealed in this paper. There is given a new data on the tsarist censorship and the terms of censoring the calendars. There are stressed some aspects of the work of L. Ivinskis as the editor of the calendars, his share in distributing them. Some short news are given about the preparing of calendars at the time when the Lithuanian press was prohibited. A new document which shows that L. Ivinskis tried to renew the edition of calendars in 1880 is disclosed.